Padrão de resistência a antimicrobianos e genes de virulência em salmonella enteritidis formadoras de biofilme - Silva, Carla Ferreira da (2014)
The Salmonella Enteritidis is one of the most isolated pathogens in outbreaks of foodborne diseases, and the most prevalent and most isolated in outbreaks of salmonellosis. The choice of the appropriate sanitizer in food industries is essential to prevent the dissemination of microbial contamination and control of biofilms on surfaces. The concern about antimicrobial resistance is also extremely important. Furthermore, the interaction which occurs between Salmonella and their hosts is multifactorial and may be related to virulence genes. Twenty samples of S. Enteritidis as the formation of biofilms, antibiotic resistance and sanitizers were tested. We tested the sanitizing resistance to biguanide concentrations 0.6%, 1.0% and 1.5%, peracetic acid at concentrations 0.1%, 0.5% and 1.0%, and quaternary ammonia at concentrations of 0, 3%, 1.0% and 2.0%. For tests of antimicrobial resistance the cultures were evaluated front 10 mcg ampicillin, 30 mcg cephalexin, 30 mcg chloramphenicol, 5 mcg enrofloxacin, 15 mcg erythromycin, 30 mcg neomycin, 25 mcg sulphazotrim, 300 mcg sulfonamides. Furthermore, in 18 of these samples was evaluated the presence of hilA, avrA, invA, sivH, sopE, spiA, agfA, lpfA, sefA and spvC genes. In the results obtained for the biofilm formation, 25% of samples were strongly biofilm formers, 35% moderately formers, 35% weakly formers and 10% not biofilm formers. All S. Enteritidis from outbreaks of foodborne diseases and 80% from poultry products produced biofilm. In sanitizers, quaternary ammonia and peracetic acid were effective at all concentrations and at all times, but tests with biguanide resulted in resistance in the time of 1 minute at concentrations 0.6%, 1.0% and 1,5%, at time 5 minutes at concentrations of 1.0% and 1.5% and at time 10 minutes at concentrations of 0.6% and 1.0%. As for antimicrobial susceptibility testing, 10 samples of S. Enteritidis presented pattern of multidrug resistance to the antibiotics tested. In relation to the active principles, 25% of S. Enteritidis were resistant to ampicillin, 5% to cephalexin, 55% to enrofloxacin, 90% to erythromycin, 80% to neomycin, 5% to sulphazotrim, 70% to sulfonamides. There was 100% sensitivity to chloramphenicol. Besides the formation of biofilms, 50% of S. Enteritidis were multiresistant to antimicrobials been tested, and 20% were also resistant to biguanide. The hilA, avrA, invA, sopE, spiA, agfA, lpfA, sefA and spvC genes were present in 100% of S. Enteritidis and sivH gene was present in 89%. Although all samples be S. Enteritidis there was changes in genetic profile, being the profile 1 the most prevalent, with 16 samples possessed all genes. These results denotes great relevance due to the possibility of permanence of these microorganisms in food manipulation environments in the form of biofilms and, in the case of transmission to humans, present more difficulty in treatment due to the multidrug resistance. Further than, the presence of virulence genes may be one reason for the higher virulence of Salmonella Enteritidis in cases of outbreaks of foodborne diseases